PENGARUH PROGRAM KESEHATAN dan KESELAMATAN KERJA (K3) TERHADAP PRODUKTIVITAS TENAGA KERA ( STUDI pada PT WIJAYA KARYA PROYEK PEMBANGUNAN JALAN TOL BALIKPAPAN-SAMARINDA SECTION 4) - Dewi Selvinaningrum (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
This study aims to determine the significance of the effect of the occupational health and safety program (k3) on labor productivity at PT Wijaya Karya (study on the Balikpapan-samarinda toll road construction project section 4), as well as to find out and analyze the most influential effect on labor productivity at PT wijaya Karya (study on the balikpapan-samarinda toll road construction project section 4). The sampling technique used was probability sampling (simple random sampling). The number of samples used was 79 respondents. Primary data obtained by distributing questionnaires to the visitors. Secondary data obtained by conducting field observations. Data analysis using multiple linear regression techniques with the help of SPSS 22 statistical software. The results of this study are the variables of occupational health and work safety simultaneously and partially have a significant effect on labor productivity. And the most influential variable is work safety. High level of safety creates conditions that support comfort and excitement of work, so that human factors can be harmonized with the level of efficiency for the continuity of the work process.